Policy analysis of sports development in terms of achievement, policy, nursery of young athletes, South Papua as part of the new autonomous region, (DOB) - Emanuel Lewar; Subagyo Subagyo; Aris Fajar Pambudi; Syamsudin Syamsudin; Thadius Yambedoan; Carolus Wasa; Hendra Jondry Hiskya (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective. This study aims to analyze sports coaching policies in South Papua as a new autonomous region (DOB), focusing on sports policy, athlete nurturing, facilities and infrastructure, institutional support, and athlete achievements.